(untitled) (The Pakistan Development Review, 2000)
The purpose of the study is to trace and review the growth and development of the Pakistani Equity Market. The capital markets in Pakistan has been undergoing a major restructuring programme. Number of measures have been taken to liberalise investment procedures and encourage capital formation through stock exchanges, enlarge size and depth of capital markets. We are witnessing globally a remarkable pace of change from a social and economic perspective. Capital markets being driven by the floods of competition and technology are experiencing so many new challenges and changes inducing them to incline more towards complex structures which would not have been considered possible few time back. Capital markets play an important role in the economic development of emerging capital markets. These markets are an important and efficient conduit to channel and mobilise funds to enterprises, and provide an effective source of investment in the economies they serve. Well functioning markets ensure that both corporations and investors get or receive fair prices for their securities. Their role for mobilising savings for investment in productive assets is acute which subsequently enhance the country’s long term growth prospects. Therefore we can deduce here that their role is like a major catalyst for transformation of the country’s economy into a more efficient and competitive emporium within the global workroom.